Why Do the Patients with Hirschsprung Disease Get Redo Pull-Through Operation? - Han, Ji-Won; Youn, Joong Kee; Oh, Chaeyoun; Kim, Hyun-Young; Jung, Sung-Eun; Park, Kwi-Won (European Journal of Pediatric Surgery, 2019)
Introduction The treatment of Hirschsprung disease (HD) is pull-through (PT) surgery. Redo PT can be performed in 1 to 10% of patients after initial PT. In this study, we reviewed the causes and associated factors of redo PT.Materials and Methods We retrospectively reviewed medical charts of 657 patients with HD who underwent surgeries between September 1979 and January 2016. The indications for redo PT are as follows. First, there were persistent obstructive symptoms after the first operation, (1) with transition zone shown definitely on contrast study, (2) with anatomic problems, and (3) obstructive symptoms persist despite conservative or nonredo surgical treatment without (1) and (2). We analyzed the causes and associated factors of redo PT.Results A total of 49 (7.5%) patients underwent redo PT. Among them, 41 and 8 patients underwent PT twice and three times, respectively. Among 57 cases of redo, the causes of redo included pathologic problem (n = 28)—aganglionosis (n = 20), hypoganglionosis (n = 4), immature ganglion cell (n = 4)—or anatomic problem (n = 21)—stricture (n = 13), fistula and/or abscess (n = 8) at anastomosis. Comparing associated factors between the nonredo and redo groups, the redo group had longer initial PT operation time (p = 0.001), more postoperative complications (p < 0.001), and more transanal endorectal PT (TERPT) approach as initial PTs (p < 0.001). According to causes of redo, the anatomic problem group underwent more third PTs than the pathologic problem group (p = 0.010).Conclusion Approximately 7.5% of patients experienced redo PT. The cause of redo included pathologic (n = 28) or anatomic problem (n = 21). Longer operation time, more complications, and TERPT were associated with redo. The anatomic problem group underwent more third PTs than the pathologic problem group.
Keywords: colorectal; pediatric; gastrointestinal; Hirschsprung disease